Exploring the Self-Perceptions of Filipino Teachers on Their Community Engagement Competency - Santos, Patricia (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2024)
Community engagement (CE) is a necessary teacher competency. Given its importance, this research aims to assess the self-perceptions of Filipino teachers on their CE competency and see if there are significant differences in their assessment based on different factors. Using a researcher-made survey, teacher participants were asked to rate how well they demonstrated each action statement in the instruments based on their perception of their community engagement competency from the School Year 2019 – 2020. Comparisons on the total community engagement scores were then compared based on the school type, grade level assignment, and length of teaching service. Results showed that Filipino teacher survey respondents (n=31) perceived themselves to be able to demonstrate the identified CE behavioral indicators, and their identified highest and lowest-rated behavioral indicators may be used as a springboard for further training needs analyses for CE professional development inputs. Statistical analyses showed no significant differences in the CE scores of the respondents based on all the identified factor groupings. This study aims to contribute to measuring CE competency among Filipino teachers.